KEMBAR MAYANG DALAM UPACARA ADAT PERKAWINAN JAWA DI DESA NAMBAHREJO - Aurora Nandia Febrianti; Iskandar Syah; Wakidi Wakidi (FKIP UNIVERSITAS LAMPUNG, 2013)
This study was aimed to explore the meaning of Kembar Mayang symbol in traditional Javanese wedding ceremony. The method used in this study was the deskriptif method. The data collecting technique was done by observation technique, interview and literature. The data analysis technique that was used was qualitative data analysis technique. Based on the results of research, Kembar Mayang is one of the symbol that is included in a series of Panggih ritual ceremonies in Javanese traditional wedding ceremony. Kembar Mayang is made by someone who is expert in making Kembar Mayang and know the meaning of each symbol contained in the Kembar Mayang. Kembar Mayang has always made a pair of twins, the Kembar Mayang bride and Kembar Mayang groom. The meaning that contained in Kembar Mayang is about advice for the bride and groom in undergoing the new life. Penelitian ini bertujuan untuk mencari makna simbol Kembar Mayang dalam upacara adat perkawinan Jawa. Metode yang digunakan dalam penelitian ini adalah metode deskriptif. Teknik pengumpulan datanya adalah teknik observasi, wawancara dan studi pustaka. Teknik analisis datanya merupakan teknik analisis data kualitatif. Berdasarkan hasil penelitian yang telah dilakukan, Kembar Mayang merupakan salah satu simbol yang disertakan dalam upacara panggih pada serangkaian ritual upacara adat perkawinan Jawa. Kembar Mayang dibuat oleh seseorang yang ahli dalam pembuatan Kembar Mayang dan mengetahui makna yang terkandung dalam setiap simbol pada Kembar Mayang. Kembar mayang selalu dibuat sepasang, yaitu kembar mayang perempuan dan kembar mayang pria. Makna yang terkandung dalam Kembar Mayang berisi tentang nasehat bagi calon pengantin dalam mengarungi hidup baru. Kata kunci: kembar mayang, makna, upacara adat perkawinan Jawa